Hakikat Pengembangan Kurikulum Di MI/SD - Nurfitri Apriliani; Zunidar Zunidar; Mischa Danira S. Maha; Slamet Arianto (Jurnal Sains, Teknik, Ekonomi, dan Pendidikan, 2026)
The curriculum has an important position in the implementation of education at Madrasah Ibtidaiyah/Elementary Schools (MI/SD), as it serves as a guideline for teachers in conducting the learning process at school. This paper discusses the roles, functions, dimensions, and position of the curriculum, as well as its differences from learning at the MI/SD level. The discussion is carried out by reviewing various sources related to curriculum and learning. The curriculum functions as a guide and direction in achieving educational goals and maintaining coherence among educational components within the school. Its functions include adaptation, integration, differentiation, preparation, selection, and diagnostic functions. From its dimensions, the curriculum can be understood as a plan or document, as a system, and as a field of study. In addition, the curriculum serves as a link between educational goals and the implementation of classroom learning. The discussion shows that curriculum and learning are two different but closely related concepts. The curriculum is conceptual in nature because it is a plan, whereas learning is practical because it represents the implementation of the curriculum itself. Therefore, the success of learning in MI/SD is largely determined by how the curriculum is designed and implemented in practice.